Réponses

Meilleure réponse !
2014-04-15T21:37:17+02:00
Bonsoir
g(x) = (2x+1)² - 9 
1) Développer 
g(x) = 4x² + 4x + 1 - 9 = 4x² +4x - 8 
2) Factoriser
g(x) = (2x+1)² - 9 = (2x+1)² - 3²     forme de a²-b² = (a-b)(a+b)
g(x) = (2x+1-3)(2x+1+3) = (2x-2)(2x+4) 
3)
g(0) = 4(0)²+4(0)-8 = -8 
g(-1) = (2(-1)-2)(2(-1)+4) = (-4)(2) = -8 
g(V5) = 4(V5)² +4(V5) - 8 = 20 + 4V5 - 8 = 12 + 4V5 
4)
g(x) = 0  
(2x-2)(2x+4) = 0      pour x = 1    ou x = -2 

g(x) = -10 
(2x+1)²-9 = -10 
(2x+1)² = -1    solution impossible car un carré est toujours positif

g(x) = 1 
(2x+1)²-9 = 1
(2x+1)² = 10               (V veut dire racine)
2x+1 = V10   pour x = (V10-1)/2 = 1.08 arrondi 
ou
2x+1 = -V10    pour x = (-V10 - 1) / 2 = - 2.08 arrondi